(untitled) (Damascus University Journal of agriculture sciences, 2024)
Abstract: This study was conducted at The Department of Food Science-Faculty of Agriculture - Damascus University with the aim of preparing a caffeine- free coffee surrogate using different levels of date seeds, barley and chicory roots, and studying some of its chemical and sensory indicators, in addition to estimating the Caffeine content, total phenols, total flavonoids and DPPH radical scavenging activity. The results showed that all prepared mixtures were free of caffeine, while the values of total phenols ranged between (5.08-36.46 mg GAE/g on dw), and the values of total flavonoids ranged between (2.95-15.95 mg QE/g on dw), and the percentage of antioxidant activity ranged from 45.56% to 77.99%. The results of sensory evaluation showed that there were no significant differences between the mixtures with regard to color, and there were no significant differences between the roasted date seeds, roasted barley and mixture (50% roasted barley with 50% roasted date seeds) in terms of taste with values (3.92, 3.33, 3.67) respectively, and there were no significant differences between roasted date seeds and mixtures (25% roasted date seeds with 75% roasted barley), (50% roasted barley with 50% roasted date seeds), and (65% roasted barley with 15% roasted date seeds and 20% roasted chicory roots) in terms of smell with values (3.67, 3.17, 3.08, 3) respectively. Key Words: Coffee Surrogate, Date Seeds, Barley, Chicory Roots, Total Phenols, Antioxidant Activity.